Food Preference of Bullet Tuna (Auxis rochei Risso, 1810) in Prigi Coast of Trenggalek Regency, East Java - Bella Pradita Agustina; Ana Ariasari; Tony Budi Satriyo; Eko Setyobudi (Journal of Tropical Biodiversity and Biotechnology, 2023)
As a commercial fish, bullet tuna is constantly caught in purse seine fisheries to provide economic benefits for coastal communities. Biological information such as food preference has to be known due to their sustainability in the future. This research aims to figure out the food composition and preference of bullet tuna (Auxis rochei Risso, 1810) in Prigi Coast, Trenggalek Regency East Java. A total of 294 fish landed by purse seine fishermen have been collected from March up to May 2018. Each individual was measured in its total length and weight, then was dissected for sex determination,  measured the length of intestine, and analyse the stomach content. The data analysis encompasses frequency distribution of total length, relative gut length, frequency of occurrence, index of preponderance, trophic level, niche breadth, and food overlapping. The research result indicates that the main foods of Auxis rochei are fish and crustacean, while the complementary and additional foods were copepod, mollusc, annelid, and debris. Bullet tuna was a carnivorous fish with the trophic level of 3.7 and shows the existence of competition for food resources. Overlapping of feeding occurred in the 19-20 cm long group against the 23-24 cm long group in male fish and the 19-20 cm size group against the 21-22 cm length group in female fish. Bullet tuna use the same feed resources among the size groups of fish, where females use feed over a wider area than males.